Astrocytic tau pathologies in aged human brain. Issue 3 (1st April 2019) - Okamoto, Koichi; Amari, Masakuni; Fukuda, Toshio; Suzuki, Keiji; Takatama, Masamitsu
Abstract : Argyrophilic and tau‐positive abnormal structures in astrocytes are frequent in aged brains, with a new nomenclature of aging‐related tau astrogliopathy (ARTAG) proposed. The two major cytomorphologies of ARTAG are thorn‐shaped astrocytes (TSA) and granular or fuzzy tau immunoreactivity in processes of astrocytes (GFA). We selected 28 cases in which many AT8‐identified astrocytic tauopathies were observed in the central nervous system from 330 routine aged autopsied cases, including Alzheimer's disease. AT8‐identified and Gallyas silver staining‐positive TSA were observed in subpial, subependymal, perivascular areas as well as white matter. These TSA were 4‐repeat (4R) tau‐positive. In contrast, 3‐repeat (3R)‐tau was negative in TSA, but positive in short thick cell processes, likely neuropil threads, in subpial and subependymal areas. The frequency of 3R‐tau‐positive processes was variable. Small dot‐like AT8‐identified astrocytic processes surrounding vessels in the neuropil were also positive for 4R‐tau, but negative for 3R‐tau. GFA in cerebral gray matter were AT8‐identified and Gallyas‐positive, and positive for 4R‐tau but negative for 3R‐tau. In this study, we did not identify 3R‐tau+/4R‐tau+ or 3R‐tau+/4R‐tau– astrocytes. Further studies are needed to clarify the nature and progression of glial tau‐positive structures in ARTAG.